Tilted pillar array fabrication by the combination of proton beam writing and soft lithography for microfluidic cell capture: Part 1 Design and feasibility. Issue 3 (1st October 2015) - Rajta, Istvan; Huszánk, Robert; Szabó, Atilla T. T.; Nagy, Gyula U. L.; Szilasi, Szabolcs; Fürjes, Peter; Holczer, Eszter; Fekete, Zoltan; Járvás, Gabor; Szigeti, Marton; Hajba, Laszlo; Bodnár, Judit; et al.
Abstract : Design, fabrication, integration, and feasibility test results of a novel microfluidic cell capture device is presented, exploiting the advantages of proton beam writing to make lithographic irradiations under multiple target tilting angles and UV lithography to easily reproduce large area structures. A cell capture device is demonstrated with a unique doubly tilted micropillar array design for cell manipulation in microfluidic applications. Tilting the pillars increased their functional surface, therefore, enhanced fluidic interaction when special bioaffinity coating was used, and improved fluid dynamic behavior regarding cell culture injection. The proposed microstructures were capable to support adequate distribution of body fluids, such as blood, spinal fluid, etc., between the inlet and outlet of the microfluidic sample reservoirs, offering advanced cell capture capability on the functionalized surfaces. The hydrodynamic characteristics of the microfluidic systems were tested with yeast cells (similar size as red blood cells) for efficient capture.